2023
DOI: 10.3389/fnagi.2023.1245904
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the role of herpes simplex virus 1 in Alzheimer’s disease

Shu Feng,
Yongzhen Liu,
Yu Zhou
et al.

Abstract: Alzheimer’s Disease (AD) is an aging-associated neurodegenerative disorder, threatening millions of people worldwide. The onset and progression of AD can be accelerated by environmental risk factors, such as bacterial and viral infections. Human herpesviruses are ubiquitous infectious agents that underpin numerous inflammatory disorders including neurodegenerative diseases. Published studies concerning human herpesviruses in AD imply an active role HSV-1 in the pathogenesis of AD. This review will summarize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 162 publications
0
4
0
Order By: Relevance
“…Other studies also showed that inhibition of glycolysis resulted in a significant decrease in HSV propagation [30,31]. There are differing results regarding the impact of HSV infection on the TCA cycle and oxidative phosphorylation including the potential shift from the TCA cycle and oxidative phosphorylation to the pentose phosphate pathway [32]. However, it was also shown previously that the HSV-1 UL43 protein was localized to the mitochondria, and increased aerobic oxidation and oxidative phosphorylation of glucose resulted in an overall increase in ATP generation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also showed that inhibition of glycolysis resulted in a significant decrease in HSV propagation [30,31]. There are differing results regarding the impact of HSV infection on the TCA cycle and oxidative phosphorylation including the potential shift from the TCA cycle and oxidative phosphorylation to the pentose phosphate pathway [32]. However, it was also shown previously that the HSV-1 UL43 protein was localized to the mitochondria, and increased aerobic oxidation and oxidative phosphorylation of glucose resulted in an overall increase in ATP generation [33].…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 is a ubiquitous virus that affects more than 80% of people over 65 across the globe [ 29 ]. There exists a detailed and eloquent review by Shu Feng and colleagues that really delves into the details surrounding HSV-1 in AD [ 30 ]. We decided to add to the discussion, mainly in our future directions discussion, Section 4.1.4 ., below.…”
Section: Elaboration Of Selected Viral Examples Implicated In Ad and ...mentioning
confidence: 99%
“…Currently, some studies suggest a potential association between HSV-1 and AD, but the nature of this association remains unclear. There are several recent reviews that have listed and discussed many studies on the potential importance of HSV-1 in AD development [ 30 , 49 , 50 , 51 ]. Herein, we have dawn on some well-known or well-understood examples that we hope to continue to add to this perspective on HSV-1 and the infection process.…”
Section: Elaboration Of Selected Viral Examples Implicated In Ad and ...mentioning
confidence: 99%
“…Although somewhat controversial, increasing experimental and epidemiological evidence indicates that viral infections are an environmental risk factor for the development of neurodegeneration and neurological sequelae [9]. For example, neurotropic pathogens, such as human herpes virus (HHV), herpes simplex virus (HSV), hepatitis C virus (HCV), cytomegalovirus, varicella-zoster virus, and Epstein-Barr virus are associated with Alzheimer's disease (AD) neuropathology [10][11][12][13]. Although previous studies do not indicate VEEV is related to neurodegeneration, VEEV neurological sequelae share progressive characteristics of neurodegenerative disorders including cognitive, motor, or sensory deficits [4,14,15].…”
Section: Introductionmentioning
confidence: 99%